Deposition and Characterization of Zn–Sn–O (ZSO) Thin Films with Novel Optical Properties. Issue 8 (17th February 2022) - Xu, Linhua; Luo, Xiaoqiang; Qian, Haisu; Zheng, Gaige; Xian, Fenglin; Su, Jing
Abstract : The ZnSnO film is fabricated using sol–gel process, and the change of its morphological feature, structure and optical properties with increasing heat‐treatment temperature is studied. Scanning electron microscopy (SEM) images display that the ZnSnO films consist of two different layers of component. The surface layer is crystalline zinc oxide (ZnO), and the bottom layer is amorphous Zn x Sn y O z ternary compound. When the ZnSnO film carries out a heat‐treatment at 350 and 400 °C, the thickness and grain morphology of the ZnO layer are hardly changed. However, some pyramid‐shaped grains appear on the film surface, when the temperature rises to 450 °C. These ZnSnO films exhibit interesting optical properties: they all have the luminescence features of ZnO and the bandgap width similar to tin oxide (SnO2 ). The changes in the size and shape of the ZnO grains in the surface layer lead to obvious changes in the optical properties: the ultraviolet emission of the ZnSnO films is greatly enhanced, and the transmittance is gradually increased. The ZnSnO film with a special structure, namely, a double‐layer including a highly crystalline ZnO layer and amorphous Zn x Sn y O z layer, has potential applications in optoelectronic devices. Abstract : The ZSnO film is fabricated using sol–gel process, and the change of its morphological feature, structure, and optical properties, with increasing heat‐treatment temperature, is studied. The changes in the size and shape of the ZnO grains in the surface layer lead to obvious changes in optical properties: The ultraviolet emission is greatly enhanced, and the transmittance is gradually increased.